2019
DOI: 10.1101/626697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repurposing the aldose reductase inhibitor and diabetic neuropathy drug epalrestat for the congenital disorder of glycosylation PMM2-CDG

Abstract: Phosphomannomutase 2 deficiency, or PMM2-CDG, is the most common congenital disorder of glycosylation affecting over 1,000 patients globally. There are no approved drugs that treat the symptoms or root cause of PMM2-CDG. In order to identify clinically actionable compounds that boost human PMM2 enzyme function, we performed a multi-species drug repurposing screen using a first-ever worm model of PMM2-CDG followed by PMM2 enzyme functional studies in PMM2-CDG patient fibroblasts.Drug repurposing candidates from… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…None of these molecules resembles natural ligands of PMM2. α -cyano-4-hydroxycinnamic acid enhanced PMM2 enzymatic activity in fibroblasts derived from patients and in a nematode model of PMM2-CDG [25]. Since α -cyano-4-hydroxycinnamic acid shares the carboxylic acid-containing pharmacophore of aldose reductase inhibitors, Perlestein and co-workers [25] tested other commercially available inhibitors of the same enzyme in the nematode model and fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…None of these molecules resembles natural ligands of PMM2. α -cyano-4-hydroxycinnamic acid enhanced PMM2 enzymatic activity in fibroblasts derived from patients and in a nematode model of PMM2-CDG [25]. Since α -cyano-4-hydroxycinnamic acid shares the carboxylic acid-containing pharmacophore of aldose reductase inhibitors, Perlestein and co-workers [25] tested other commercially available inhibitors of the same enzyme in the nematode model and fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…α -cyano-4-hydroxycinnamic acid enhanced PMM2 enzymatic activity in fibroblasts derived from patients and in a nematode model of PMM2-CDG [25]. Since α -cyano-4-hydroxycinnamic acid shares the carboxylic acid-containing pharmacophore of aldose reductase inhibitors, Perlestein and co-workers [25] tested other commercially available inhibitors of the same enzyme in the nematode model and fibroblasts. They found that epalrestat, which is a safe, orally bioavailable, and brain penetrant aldose reductase inhibitor used to treat diabetic peripheral neuropathy, rescued PMM2 enzymatic activity in both species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luckily the manual scoring format provide a z′-score of >1.5 with 41 hits that replicated in more than two experiments ( SI Figure 2.3 ). The low hit discovery rate in our fly screen may not be surprising as drug exposure related artifacts such as reduced feeding relating to the preference of flies for each compound, uncertainty about the amount of food consumed, compound stability in fly food, stochasticity due to small numbers of animals per well, and tissue concentration achieved by each compound are known (Qi, et al, 2015; Ja, et al, 2007; Marx, 2015; Iyer, et al, 2019). To enable our ability to compare the fly hits with the orthogonal screening efforts in worms and fibroblasts, we chose to be more inclusive of our hits for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…We are concerned about the futility of spending time and effort to pursue additional studies of mannose in PMM2-CDG, where there is very little evidence for efficacy. We note that there have been a number of recent advances in approaches to treat PMM2-CDG [13], including: a recently reported open-label study demonstrating improvement in ataxia with acetazolamide [14], pharmacologic chaperones [15] or aldose reductase inhibitors identified through a drug-repurposing screen [16], and mannose-1-phosphate replacement therapies intended to bypass the PMM2-dependant biosynthetic step [13].…”
Section: Priorities For Advancing a Therapy For Pmm2-cdgmentioning
confidence: 99%